Política cultural no Brasil: do Plano Nacional de Cultura às (micro) ações descentralizadas - Silva, Alessandro Antonio da (2017)
The purpose of this thesis is to analyse the Nacional Cultural Plan PNC [Plano Nacional de Cultura] considering the detection of some reasons that are preventing the establishment of a cultural policy by the plan in Brazil. With the support of some works of Michel Foucault (1926 – 1984), specially the Biopolitics Course; by Pascal Gielen (1970) about Creativity and other Fundamentalisms; of political action present at Homo Sacer figure, by Giorgio Agamben (1942); of Immunity approach at Roberto Esposito (1950) work; and the concept of Multitude by Antonio Negri (1933), the thesis starts with the governmentality idea and the analyse of economy and politics relations fortification to search the comprehension of the problems not only in the PNC constitution, but also at neoliberals contexts that engender it (and that emerge from it). Besides, authors that analyse Brazilian cultural policy and cultural economy are mentioned. The research corpus also assembles some cultural actions proposed in small Brazilian cities (not big ones, like Rio de Janeiro and São Paulo), where the situation is much more difficult. The expected result is the study of the problems that are preventing the construction of a national cultural policy, acting in several directions that involve communication, economy and politics nets, promoting desubjetivation and thanatopolitics effects instead of politics for life